Öffentliche Vernunft? Die Wissenschaft in der Demokratie - Hinsch , Wilfried; Eggers, Daniel (Edition Wissenschaft & Demokratie, 2019)
There is no society that is not affected by modern science and its consequences. There is also no serious hope that global challenges such as climate, inequality or migration can be tackled without scientific research and reflection. Every society and every government is therefore dependent on science. For democracies, however, the question of the relationship between politics and science arises again in a special way, since science there appears to be something that concerns everyone and must therefore be publicly negotiated. The volume 'Public Reason? Science in Democracy 'addresses the question of the difficulties encountered by the ideal of a public and reason-led discourse on the relevance of scientific results in modern democracies. Based on questions as diverse as the problems of scientific policy advice, the relationship between science and the media, the possibilities and limits of citizen science and the role of ethics and politics in the university, the contributions presented open up new perspectives on the complex relationship between science, politics and media and non-media public.